2018
DOI: 10.1002/chem.201801356
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ethylene Epoxidation on a Promoted Ag/α‐Al2O3 Catalyst—The Effects of Product and Chloride Co‐Feeds on Rates and Selectivity

Abstract: The overall chloriding effectiveness factor (Z*), defined as the ratio of ethyl chloride concentration in parts per million to the sum of ethylene and ethane concentration in mole percent multiplied by a weighting factor to account for their efficacy in removing chlorine-adatoms from the surface, was used as a parameter to account for the effects of chlorine on the kinetics of ethylene epoxidation on a highly promoted 35 wt % Ag/α-Al O catalyst. An increase in O order (≈0.7 to 1) and a decrease in C H order (≈… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 61 publications
(186 reference statements)
5
71
0
Order By: Relevance
“…Harris et al recently reported on the fate of alkyl chloride species in the epoxidation of ethylene over Ag/α-Al 2 O 3 , in which Cl is deposited on the surface by a cofed alkyl chloride and subsequently removed via oxychlorination of ethane. [53,56] Similar chemistry likely occurs in the propylene epoxidation system reported herein, although even with excellent overall mass balance, we were unable to detect oxychlorination products, likely due to concentrations below the detection limit.…”
Section: Catalyst Reactivity and Feed Modifier Effectsmentioning
confidence: 52%
See 1 more Smart Citation
“…Harris et al recently reported on the fate of alkyl chloride species in the epoxidation of ethylene over Ag/α-Al 2 O 3 , in which Cl is deposited on the surface by a cofed alkyl chloride and subsequently removed via oxychlorination of ethane. [53,56] Similar chemistry likely occurs in the propylene epoxidation system reported herein, although even with excellent overall mass balance, we were unable to detect oxychlorination products, likely due to concentrations below the detection limit.…”
Section: Catalyst Reactivity and Feed Modifier Effectsmentioning
confidence: 52%
“…[52] In 2018, it was shown that in an industrially relevant catalyst (Ag/ α-Al 2 O 3 ), the reaction orders in O 2 and C 2 H 4 depend on the amount of Cl deposited on the surface during the reaction, where more chloride increases the reaction order in O 2 up to a maximum of 1, and diminishes the reaction order in C 2 H 4 from 0.5 to sub-zero. [53] The clear importance of feed modifiers and promoters in alkene epoxidation makes kinetic studies under such conditions of vital importance.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a key to a selective state of the catalyst is to minimize the atomic oxygen on the surface. In industrially applied systems this is realized by promoters . Due to the strong Ag−O interaction of nanoparticles (higher oxophilicity), not only the activation phase is intriguing, but also the oxygen poor Ag surface might accumulate locally an excess of adsorbed oxygen leading to a lowered S (EO) and E A of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of chlorinated hydrocarbons as promoters for ethylene epoxidation is widely applied on the industrial scale and allows to enhance the selectivity towards the desired ethylene oxide [11,81,82]. The mainstream opinion is that the combination of electronic and structural effects of chlorine allows to tailor the balance between different oxygen species (electrophilic and nucleophilic in nature) and, correspondingly, the reaction rates of different reaction pathways [83][84][85][86][87]. Depending on the coverage, chlorine can: (i) adsorb on surface or penetrate into subsurface at low coverages or (ii) completely poison (via blockage of oxygen chemisorption) the catalyst in case of high-concentration co-feeding [81,86,[88][89][90].…”
Section: Promotion By Ethyl Chloridementioning
confidence: 99%